The Negrita of the Yucatan Peninsula: A ritual with multiple identities - re, Arianna (Comparative Cultural Studies: European and Latin American Perspectives, 2025)
This article analyzes the ritual surrounding La Boxita, a doll that plays a central role in a popular festivity in Hunucmá, Yucatán, during the celebration of Corpus Christi. Through an anthropological and historical lens, it explores how this female figure—crafted with Indigenous features, dark skin, and dressed in mestiza attire—embodies multiple layers of collective memory: from Afro-descendant and Indigenous presence to the symbolic construction of the Yucatecan woman. The discussion unfolds in three analytical levels: the historical construction of regional symbols, the ritual logic of destruction as purification, and the historical invisibilization of women and Afro-descendants. The article proposes that La Boxita is a liminal figure that articulates tensions between visibility and erasure, the sacred and the profane, festivity and politics, serving as a living archive of denied memories and a symbolic field of struggle.